Development of mangrove tourism area through making tourism umbrellas as well as private society preparation in Regemuk village Pantai Labu Sub-Distric Deli Serdang District - Bakti, Darma; Rosmayati; Rahmawati, Nini (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Regemuk Village has the potential to be developed into a new tourist destination village. The village which is located along the coastline of Deli Serdang Regency is geographically the closest village to Medan City and the location is adjacent to Kuala Namu Airport. One of the advantages of this village is the presence of a stretch of mangrove forest which is still quite good along the 7 km coastline. The development of the village into one of the beach tourism destinations has been a long-term discourse, but until now it has not been implemented. To realize this, it is necessary to explore the development of supporting facilities in order to initiate the development of the village into a tourist destination mangrove tourism area. Seeing this reality, the USU PPM Implementation Team through the Professor Serves Program Scheme helped community problems by developing mangrove forest areas and providing supporting facilities, namely beach tourism park umbrellas. The existence of this facility is expected to help increase the carrying capacity of this newly formed tourist site. This program will encourage the spirit of the realization of mangrove tourism areas and be able to produce other downstream tourism products.